GAMBARAN PENGETAHUAN IBU TENTANG ALAT KONTRASEPSI IUD DIDUSUN KRAMAT DESA SEBANEN KECAMATAN KALISAT KABUPATEN JEMBER - Eka P, Veryudha (JURNAL KEPERAWATAN SEHAT, 2016)
IUD is one type of contraceptive. Mechanism of action of IUD sare researched small wireagenci esissued concentration into the uterine cavity than IUD causean inflammatory reaction as usual, also inhibit the efficacy an hidrasi fostase carbon and alkali. The Purposive of this research to know the description of knowledge of mothers aged 20-35years of IUD contraception in Dusun kramat Desa Sebanen Kecamatan Kalisat. The study design used was descriptive. The population in this study were mothers aged 20-35years by 45 respondents, a sample of 40 respondent used the way from using probability sampling methods ofthe type of simple random sampling. The collected data is processed by way of editing, coding, scoring, andtabulating. Then the dataare presented usinga frequencydistribution table.In the present study showed thatas many as 22 respondents(55%). It is concluded that highly educated respondents would be easy to absorb in formation about contraceptive IUD, so knowledge of IUD contraception is better. In contrastKey words: knowledge, ContraceptionIUD, Mrs.